2021
DOI: 10.3846/aviation.2021.15889
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of Partial Regular Microreliefs Formed on Rotary Body Face Surfaces

Abstract: The basic regularities in the influence of processing parameters on the geometrical characteristics of the partially regular microreliefs, formed on the rotary body face surface, are established. Combinations of partially regular microreliefs are formed by using a contemporary CNC milling machine, and an advanced programing method, based on previously developed mathematical models. Full factorial experimental design is carried out, which consist of three factors, varied on three levels. Regression stochastic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Meanwhile, in the case of the perpendicular grooves, almost all the grooves were in contact with the pin surface during the tribo-test. The frictional properties depend on the depth of the textures (as this is related to the formation of the hydrodynamic lift) and the texture density [ 32 ]. Hence, the depth of the cut and distance between the textures were chosen as the factors for controlling the friction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in the case of the perpendicular grooves, almost all the grooves were in contact with the pin surface during the tribo-test. The frictional properties depend on the depth of the textures (as this is related to the formation of the hydrodynamic lift) and the texture density [ 32 ]. Hence, the depth of the cut and distance between the textures were chosen as the factors for controlling the friction.…”
Section: Methodsmentioning
confidence: 99%
“…The tribological properties of dimple surface texturing and groove channels have been subjected to comparison. It should be noted that the friction reduction also depends on the shape, orientations and geometric dimensions of the textures [ 29 , 30 , 31 , 32 , 33 ]. Hu et al [ 34 ] created dimples on 2024 aluminum alloy using laser texturing and reported a friction reduction with a dimple density of 8.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are constantly under development and supplemented with new data. For example, Zawada-Michałowska et al [ 24 ] pointed out that machining accuracy is influenced by the machining strategy and the direction of tool guidance, which was also described by Dzyura et al [ 25 ] and Chuchala et al [ 26 ]. This proves that milling in the direction perpendicular to the rolling direction (pre-milling) causes greater deformation than milling in the parallel direction.…”
Section: Introductionmentioning
confidence: 96%
“…Regardless of the fact that variable transmissions have already occupied a certain niche in car making, enhancing their reliability and manufacturability to extend their service life is an important task. There are a number of efforts for analysing the height-related roughness parameter R a (Wang et al 2010;Volchok et al 2002;Dzyura et al 2021aDzyura et al , 2021bDzyura et al , 2021c. The service characteristics of surfaces, in particular, the ability to retain oil, were investigated, using the group of R k parameters on the Abbott-Firestone diagram, based on surface profilograms of test specimens.…”
Section: Introductionmentioning
confidence: 99%